ICTV Virus Taxonomy Profile: Metaviridae. (13th November 2020) - Llorens, Carlos; Soriano, Beatriz; Krupovic, Mart; ,
Abstract : Metaviridae is a family of retrotransposons and reverse-transcribing viruses with long terminal repeats belonging to the order Ortervirales . Members of the genera Errantivirus and Metavirus include, respectively, Saccharomyces cerevisiae Ty3 virus and its Gypsy-like relatives in drosophilids. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Metaviridae, which is available at ictv.global/report/metaviridae .